Can the Chinese study on the normal range of FeNO in children evaluate standardized asthma treatment efficacy in 6- to 12-year-old children? - Yang, Qiuyan; Cai, Chunling; Xu, Qingrong; Zheng, Yuehong; Li, Aijun; Liu, Ying; Li, Shufang; Zhang, Yanli (Frontiers in Pediatrics, 2023)
Objective: By examining fractional exhaled nitric oxide (FeNO) levels and performing pulmonary function testing, this study explored whether the multicenter study on the normal range of FeNO in children in China can be used to evaluate standardized treatment efficacy in 6-to 12-year-old children with asthma.Methods: A total of 115 children aged 6-12 years old who were first diagnosed with asthma and received standardized asthma treatment from April 2018 to July 2022 were selected. According to the FeNO level at the first visit, the subjects were divided into different high-and low-FeNO groups according to the American Thoracic Society (ATS) guidelines and the Chinese multicenter study recommendations. The consistency of the two grouping methods and the differences between the high-and low-FeNO groups were compared after standardized treatment. The grouping method that was the most suitable for children in the cross group was discussed.There was fair consistency between the Chinese multicenter study recommendations and the ATS guidelines regarding the classification of high-and low-FeNO groups (Kappa=0.338). (ii) Repeated-measures ANOVA showed that the level of improvement in FVC%, FEV1%, FEF25%, FEF50%, and FeNO in the American high-and low-FeNO groups differed with the duration of therapy (P < 0.05), however, there was no significant difference between the Chinese groups. (iii) FEV1% and FeNO improved more after treatment in the fixed high-FeNO group than in the cross group (P < 0.05). This is a provisional file, not the final typeset articleThe Chinese multicenter study on the normal range of FeNO in children in China has a limited role in evaluating standardized asthma treatment efficacy in 6-to 12-year-old children. The ATS guidelines are currently recommended for clinical assessment of asthma treatment efficacy.